PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD NEGERI 10 SALAON TONGA-TONGA - Muliani, Eti; Ginting, Riza Dwina Br (JURNAL CURERE, 2023)
This research was carried out at SDN 10 Salaon Tonga-Tonga, Ronggur District, Samosir Regency. This research aims to improve student learning outcomes with the material I and my needs in class IV by using a cooperative learning model type course review horay. The subjects of this research were all fourth grade students at SD Negeri 10 Salaon Tonga-Tonga, with a total of 18 students. The object of this research is the use of the Cooperative Learning Model Type Course Review Horay on the material I and my needs at Class IV SD Negeri 10 Salaon Tonga-Tonga. Data collection tools are observation sheets and multiple choice tests. This research is classroom action research with a research design according to Kemmis and Mc Taggart. The data analysis used the learning implementation formula, individual learning outcomes, classical completeness and average student learning outcomes. Based on the first cycle research, it was found that the results of implementing teacher activity learning were 58% in the sufficient category and the implementation of student activity learning received a score of 69 in the sufficient category, individual learning completeness was 10 students, while classical completeness was obtained by 56% of students completing and the average score 69. Cycle II  obtained results from the implementation of teacher activity learning of 80% in the good category and the implementation of student activity learning received a score of 89 in the good category, individual learning completeness was 16 students, while classical completeness was obtained by 89% of students complete and the average score was average 79. The results of this research can be concluded that the cooperative learning model type course review horay can improve student learning outcomes in implementing learning using the Cooperative Learning Model Type Course Review Horay my material and my needs at SDN 10 Salaon Tonga-Tonga